# Solve for u -5(-5u+4)-7u=3(u-9)-5

-5(-5u+4)-7u=3(u-9)-5
Simplify -5(-5u+4)-7u.
Simplify each term.
Apply the distributive property.
-5(-5u)-5⋅4-7u=3(u-9)-5
Multiply -5 by -5.
25u-5⋅4-7u=3(u-9)-5
Multiply -5 by 4.
25u-20-7u=3(u-9)-5
25u-20-7u=3(u-9)-5
Subtract 7u from 25u.
18u-20=3(u-9)-5
18u-20=3(u-9)-5
Simplify 3(u-9)-5.
Simplify each term.
Apply the distributive property.
18u-20=3u+3⋅-9-5
Multiply 3 by -9.
18u-20=3u-27-5
18u-20=3u-27-5
Subtract 5 from -27.
18u-20=3u-32
18u-20=3u-32
Move all terms containing u to the left side of the equation.
Subtract 3u from both sides of the equation.
18u-20-3u=-32
Subtract 3u from 18u.
15u-20=-32
15u-20=-32
Move all terms not containing u to the right side of the equation.
Add 20 to both sides of the equation.
15u=-32+20
Add -32 and 20.
15u=-12
15u=-12
Divide each term by 15 and simplify.
Divide each term in 15u=-12 by 15.
15u15=-1215
Cancel the common factor of 15.
Cancel the common factor.
15u15=-1215
Divide u by 1.
u=-1215
u=-1215
Simplify -1215.
Cancel the common factor of -12 and 15.
Factor 3 out of -12.
u=3(-4)15
Cancel the common factors.
Factor 3 out of 15.
u=3⋅-43⋅5
Cancel the common factor.
u=3⋅-43⋅5
Rewrite the expression.
u=-45
u=-45
u=-45
Move the negative in front of the fraction.
u=-45
u=-45
u=-45
The result can be shown in multiple forms.
Exact Form:
u=-45
Decimal Form:
u=-0.8
Solve for u -5(-5u+4)-7u=3(u-9)-5

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top